Ultra‐Structural Alterations in In Vitro Produced Four‐Cell Bovine Embryos Following Controlled Slow Freezing or Vitrification. (21st August 2015) - Cavusoglu, T.; Popken, J.; Guengoer, T.; Yilmaz, O.; Uyanikgil, Y.; Ates, U.; Baka, M.; Oztas, E.; Zakhartchenko, V.
Summary: Cryopreservation is the process of freezing and preserving cells and tissues at low temperatures. Controlled slow freezing and vitrification have successfully been used for cryopreservation of mammalian embryos. We investigated the effect of these two cryopreservation methods on  in vitro  produced four‐cell stage bovine embryos which were classified according to their quality and separated into three groups. The first group was maintained as untreated controls ( n  = 350). Embryos of the second ( n  = 385) and the third ( n  = 385) groups were cryopreserved either by controlled slow freezing or by vitrification. Embryos in groups 2 and 3 were thawed after 1 day. Hundred embryos were randomly selected from the control group, and 100 morphologically intact embryos from the second and third group were thawed after 1 day and cultured to observe the development up to the blastocyst stage. The blastocyst development rate was 22% in the control group, 1% in the slow‐freezing group and 3% in the vitrification group. Remaining embryos of all three groups were examined by light microscopy, transmission electron microscopy and immunofluorescence confocal microscopy with subsequent histological staining procedures. Cryopreservation caused degenerative changes at the ultra‐structural level. Compared with vitrification, slow freezing caused an increased mitochondrial degeneration, cytoplasmic vacuolization, disruption of the nuclear and plasma membrane integrity, organelle disintegration, cytoskeletal damage, a reduced thickness of the zona pellucida and a formation of fractures in the zona pellucida. Further studies are required to understand and decrease the harmful effects of cryopreservation.